Seafloor features delineate Late Wisconsinan ice stream configurations in eastern Parry Channel, Canadian Arctic Archipelago. (15th March 2017) - MacLean, B.; Blasco, S.; Bennett, R.; Lakeman, T.; Pieńkowski, A.J.; Furze, M.F.A.; Hughes Clarke, J.; Patton, E.
Abstract: Multibeam imagery and 3.5 kHz sub-bottom profiles acquired from CCGS Amundsen between 2003 and 2013 by ArcticNet and the Ocean Mapping Group at the University of New Brunswick provide information on seafloor features, geology, bathymetry and morphology in eastern Parry Channel and the adjoining large channels in the Canadian Arctic Archipelago. Together these include Peel Sound, Barrow Strait, Lancaster Sound, Wellington Channel, Prince Regent Inlet, Admiralty Inlet and Navy Board Inlet. Those data are in part complemented by high resolution single channel seismic reflection profiles acquired by the Geological Survey of Canada in the 1970s and 1980s and by sediment cores that provide chronological and depositional information. The occurrence and pattern of streamlined mega-scale ridge and groove lineations (MSGLs) indicate that these waterways were occupied by glacial ice streams in the past. Chronological information from marine and adjoining terrestrial areas suggests a long history of glacial events ranging in time from Early Pleistocene to Late Wisconsinan. Seafloor morphology and MSGL trends together with terrestrial ice flow patterns indicate that ice streams flowed into Barrow Strait from Peel Sound and Wellington Channel, and ice streams in Prince Regent, Admiralty and Navy Board inlets flowed northward into and eastward along Lancaster Sound. Recession of the ice stream westward along Parry Channel occurred ∼16 cal ka BP to 10.8 cal ka BP. Thick ice-contact sediments deposited by a late ice advance from Prince Regent Inlet constitute the seabed across a large area of western Lancaster Sound. Timing for that late ice advance appears to be bracketed between the 11.5 cal ka BP lift-off of the eastern Parry ice stream north of Prince Leopold Island and the ∼10.0 cal ka BP deglaciation of Prince Regent Inlet. Seafloor morphology and lineation trends suggest that ice delivered by the ice stream in Peel Sound was the westernmost tributary to the ice stream occupying Lancaster Sound during the late Wisconsinan glaciation. Bathymetric data and MSGLs indicate that the ice stream emanating from M'Clintock Channel flowed westward. Highlights: MSGLs occur on the floors of Lancaster Sound and adjoining channels. Ice streams combined to form an eastward flowing ice stream in Lancaster Sound. Recession of the ice stream westward reached Barrow Strait by 10.8 cal ka BP. A late ice advance placed thick ice-contact sediments in western Lancaster Sound.